Pengaruh Akuntabilitas Dan Transparansi Terhadap Kinerja Keuangan Daerah Dengan Fungsi Pengendalian Internal Sebagai Variabel Moderasi (Studi kasus pada kantor BPKAD Kabupaten Sikka) - Dayak, Sebastianus Arnold Tumbuh; Sanga , Konstantinus Pati; Salvanos , Yan Yanitza (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to examine the influence of accountability and transparency on regional financial performance with the internal control system as a moderating variable(a Regency). This research used a associative approach witha causal relationship design and uses a quantitative method. Primary data were collected directly through questionnaires. The population and sample of this research consisted of all employees of the Regional Financial and Asset Management Agency Office of Sikka Regency, totaling 40 respondents. The results of the research indicated that (1) accountability has no significant effect on regional financial performance, meaning that accountability practices did not improve regional financial performance., (2) transparency has no significant effect on on regional financial performance, meaning that transparency practices did not enhance regional financial performance., (3) internal control did not moderate the relationship between accountability and regional financial performance, meaning that although both accountability and internal control were descriptively in the “very good” categoty, the presence of internal control has not been able to strengthen or weaken the relationship between accountability and financial performance., and (4) internal control did not moderatc the relationship between transparency and regional financial performance, meaning that even though budget management transparency has been well implemented and the internal control system has been implemented following with regulations, its presence did not automatically strengthen the relationship between transparency and regional financial performance,